Deep vein thrombosis in a 19-year-old patient with thrombophilia - description of the diagnosis and treatment - Michał Jerzy Terpiłowski; Jędrzej Tkaczyk; Barbara Klatka; Anna Orzeł; Dominika Janeczko; Magdalena Hołowczuk; Jan Jakub Kęsik; Marek Iłżecki (Kazimierz Wielki University, 2019)
Introduction: Deep vein thrombosis (DVT) is a condition in which a blood clot forms in one of the body's deep veins, most commonly of the leg or pelvis. Before the fourth decade of life risk of DVT is low (about 1 per 10000). After the age of 45, it rises and approaches about 5 per 1000 by the age of 80. Noteworthy is the fact, that patients with a positive family history have a higher risk of DVT at a young age. Essential risk factors for developing DVT are genetic conditions or acquired thrombophilia and positive family history, but the lack of family predisposition cannot rule out the occurrence of DVT. Standard treatment method of DVT involves intravenous anticoagulation with the use of low molecular weight heparin and compression therapy. Apart from the above-mentioned methods, we can distinguish intermittent pneumatic compression, surgical embolectomy, pharmacomechanical thrombectomy, and venous stenting. Case Report: We present a case report of 19 - year old patient who was first admitted to hospital in April 2017 urgently with symptoms of pulmonary embolism which was confirmed in angio-CT. Moreover, in the Doppler ultrasound, left common iliac vein (LCIV), left external iliac vein (LEIV) and left femoral vein (LFV) thrombosis was diagnosed. During the hospitalization, genetic tests, antibody levels, and antithrombin levels were performed for thrombophilia and systemic diseases conducive to thrombosis. In October 2017 the angio-MR of the pelvis confirmed visible pressure on the LCIV, caused by the common iliac artery, which corresponds to the May-Turner syndrome. In March 2018 he was admitted to the clinic with DVT symptoms of the left lower limb such as swelling, pain, and redness. The patient underwent venous angioplasty and stent implantation for LCIV. The patient was discharged from hospital with recommendations such as compression therapy, Doppler ultrasonography and monitoring of INR. Discussion: Venous thrombosis is a multicausal disease: more than one risk factor needs to be present before thrombosis occurs. Choice of DVT treatment method is aimed at improving the quality of life of patients depending on clinical symptoms. venous stenting for an iliofemoral occlusive disease is a safe and effective method of treatment. It can be done with excellent patency rates expected in cases of idiopathic occlusion and May-Thurner syndrome. On this basis, the legitimacy of using venous stent implantation as an effective method of treatment of recurrent DVT episodes can be confirmed, which has been used in the described case.